1997
DOI: 10.1679/aohc.60.275
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical Localization of Lysosomal Cysteine and Aspartic Proteinases, and Ubiquitin in Rat Epidermis.

Abstract: To analyze the degradation system in epidermal cells during their generation, differentiation, and cell death, immunocytochemical localization of lysosomal cysteine and aspartic proteinases, an endo-f3 in islet endocrine cells of the rat pancreas. J. Histochem. Cytochem. 36: 783-791 (1988).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 33 publications
1
18
0
Order By: Relevance
“…Until present most analyses of cathepsin expression have been performed in dermal cell culture and only two studies show expression of cathepsins B, C, D, H, L in human and rat epidermis (38,39). Our study revealed that unlike the latter cathepsins, CATS is not expressed in normal keratinocytes.…”
Section: Discussionmentioning
confidence: 55%
“…Until present most analyses of cathepsin expression have been performed in dermal cell culture and only two studies show expression of cathepsins B, C, D, H, L in human and rat epidermis (38,39). Our study revealed that unlike the latter cathepsins, CATS is not expressed in normal keratinocytes.…”
Section: Discussionmentioning
confidence: 55%
“…However, the cytoplasm of those cells showed no UB-positive reaction. Besides ALS, it was reported that UB was expressed in the nuclei of the epidermal cells [37,38]. The accumulation of ubiquitinated proteins may be the most likely cause of increased UB immunoreactivity [39].…”
Section: Discussionmentioning
confidence: 99%
“…Paraffin-embedded sections were immunostained by a method described elsewhere (16). Sections were treated with anti-Bcl-2 Ab …”
Section: Methodsmentioning
confidence: 99%